1999
DOI: 10.1021/jp992636m
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-Controlled Charge Transfer from Excited Ru(bpy)32+ into Nanosized TiO2 Colloids Stabilized with EDTA

Abstract: Transparent colloidal TiO 2 was prepared in aqueous EDTA solution. The average particle size was 7 nm, measured by TEM. In the presence of EDTA, the colloids were stable within a pH range from 2 to 10. In contrast to previous observations involving Ru(bpy) 3 2+ and TiO 2 where no emission quenching occurred up to pH 10, an efficient quenching of the excited Ru(bpy) 3 2+ ( 3 MLCT) by the colloidal TiO 2 was obtained in the presence of EDTA. A detailed kinetics investigation by laser flash photolysis showed the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 53 publications
2
11
0
Order By: Relevance
“…From the scheme we observed that the electron transfer process is feasible. Similar type of electron transfer between dyes and semiconductors has been previously reported [42][43][44][45][46].…”
Section: Mechanism Of Quenchingsupporting
confidence: 82%
“…From the scheme we observed that the electron transfer process is feasible. Similar type of electron transfer between dyes and semiconductors has been previously reported [42][43][44][45][46].…”
Section: Mechanism Of Quenchingsupporting
confidence: 82%
“…The lack of a pronounced effect of particle size under our conditions means that the competition between the oxidation of water by reaction 2 and reduction of the holes depends little, if at all, on particle size. The rate of reaction 2 is not expected to depend on particle size, because the rate of electron transfer through the TiO 2 /water interface is only little affected by the size. This conclusion applies to reduction of adsorbed oxygen and its intermediates as well as interfacial electron transfer to the holes from adsorbed molecules. Note that in an earlier publication slower reduction rates have been reported for TiO 2 particles of 1 nm diameter .…”
Section: Resultsmentioning
confidence: 96%
“…The rate of reaction 2 is not expected to depend on particle size, because the rate of electron transfer through the TiO 2 /water interface is only little affected by the size. [74][75][76] This conclusion applies to reduction of adsorbed oxygen and its intermediates as well as interfacial electron transfer to the holes from adsorbed molecules. Note that in an earlier publication slower reduction rates have been reported for TiO 2 particles of 1 nm diameter.…”
Section: And Hencementioning
confidence: 90%
“…The luminescent excited state of Ru(bpy) 2+ 3 is assigned to the metal-to-ligand chargetransfer (MLCT) state, whose properties are very sensitive to polarity and viscosity of the environment due to the MLCT character. The dynamic properties of the photoexcited state of Ru(bpy) 2+ 3 and related complexes adsorbed on semiconductors are of much interest, because the complexes in photoexcited state transfer an electron to certain semiconductors such as TiO 2 , resulting in dye sensitization and charge separation [9][10][11]. These processes are important for solar energy conversion and artificial photosynthetic applications.…”
Section: Introductionmentioning
confidence: 99%